Perspectives on labour law. 2nd ed. - Davies, Anne (Cambridge, 2009)
"Policy discussions play an important role in labour law, and labour lawyers draw on a wide range of disciplines and approaches in order to construct their arguments. This 2009 overview of the basic principles of labour law and the related policy arguments introduces two of the main perspectives used in the analysis of labour law today – human rights and economics. It offers a brief history of the influence of human rights and economics on labour law since the 1950s, explains neoclassical and new institutional economics and summarises the historical development of international human rights law. The insights of rights theorists and economists are then applied to a selection of topics in labour law, including anti-discrimination law, dismissal, working time, pay, consultation and collective bargaining, trade union membership and industrial action, in order to demonstrate the interplay between the two perspectives."